2023
DOI: 10.1042/bsr20221375
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mechanism of Cassiae semen in regulating lipid metabolism through network pharmacology and experimental validation

Abstract: Background: Multiple studies have assessed the role of Cassiae semen (CS) in regulating lipid metabolism. However, the mechanism of action of CS on non-alcoholic fatty liver disease (NAFLD) has seen rare scrutiny. OBJECTIVE: To explore the regulatory mechanism of CS on lipid metabolism in NAFLD. METHODS: Components of CS ethanol extract (CSEE) were analyzed and identified using UPLC-Q-Orbirap HRMS. The candidate compounds of CS and its relative targets were extracted from the Traditional Chinese Medicine Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Studies ( Dong, et al, 2017 ) have found that the main extracts of CS have anti-hyperlipidemia, liver protection, neuroprotection, antibacterial, anti-diabetic, antihypertensive and antioxidant effects, and have been widely used in clinical practice. Network pharmacology studies ( Huang, et al, 2023 ) have found that CS treatment of NAFLD mainly involves the key targets of PIK3CA, CASP3, A4, EGFR, APP, and reduces the expression of CASP3 and EGFR by regulating MAPK signaling pathway, significantly reducing intracellular lipid accumulation, and finally exerting the effect of regulating NAFLD. It lays a foundation for the future study of CS.…”
Section: Network Pharmacological Study On Non-alcoholic Fatty Liver D...mentioning
confidence: 99%
“…Studies ( Dong, et al, 2017 ) have found that the main extracts of CS have anti-hyperlipidemia, liver protection, neuroprotection, antibacterial, anti-diabetic, antihypertensive and antioxidant effects, and have been widely used in clinical practice. Network pharmacology studies ( Huang, et al, 2023 ) have found that CS treatment of NAFLD mainly involves the key targets of PIK3CA, CASP3, A4, EGFR, APP, and reduces the expression of CASP3 and EGFR by regulating MAPK signaling pathway, significantly reducing intracellular lipid accumulation, and finally exerting the effect of regulating NAFLD. It lays a foundation for the future study of CS.…”
Section: Network Pharmacological Study On Non-alcoholic Fatty Liver D...mentioning
confidence: 99%